New insights learned from the pulmonary to systemic blood flow ratio to predict the outcome in patients with hypoplastic left heart syndrome in the pre-Glenn stage: a single-center study - Mini, Nathalie; Zartner, Peter A.; Schneider, Martin B. E. (Frontiers in Cardiovascular Medicine, 2023)
Background To the best of our knowledge, no study has been made until now to determine whether the ratio between pulmonary and systemic blood flow (Qp/Qs) in the pre-stage II (PS2) or pre-Glenn stage can predict the outcome in patients with hypoplastic left heart syndrome (HLHS) who underwent Norwood (NW) palliation. Patients and methods From January 2016 to August 2022, 80 cardiac catheterizations in 69 patients with HLHS in NW palliation stage with modified Blalock–Taussig shunt (MBTS) were retrospectively recruited. The Qp/Qs was measured under stable conditions using the Fick formula. None of the patients were intubated. Patients were divided into two groups: Group 1 included patients who underwent planned cardiac catheterization (n = 56), and Group 2 had unplanned examination (n = 13), in which the indication for cardiac catheterization was desaturation in 11 patients and pulmonary over-circulation in two. The composite primary outcome was defined as accomplishing the planned operations (Glenn and Fontan) with freedom from death and reoperation, referring to palliative therapy or heart transplantation. The secondary outcome was freedom from transcatheter intervention in MBTS or pulmonary arteries. Results The median follow-up was 48 months (range 6–72 months). The median value of Qp/Qs in Group 1 was 1.75 (range 1.5–2.2). In Group 2, the 11 patients with desaturation, the median value of Qp/Qs was 1.25 (range 0.9–1.45). The two patients with suspected pulmonary overcalculation showed Qp/Qs of 2.3 and 2.5, respectively; a reduction of the shunt size was required. Approximately 96.4% of patients in Group 1 achieved the primary outcome compared with only 30.7% in Group 2. The need for reintervention was 1.8% in Group 1 compared with 61.3% in Group 2. There is a significant relationship between Qp/Qs and the impaired outcome (death, palliative therapy, or heart transplantation) with a p-value of 0.001, a relative risk factor of 3.1, and a 95% confidence interval of 1.4–7.1. No significant relationship between the Qp/Qs and the size of MBTS (p-value of 0.073) was noted. Conclusion The Qp/Qs in PS2 can predict outcomes in patients with HLHS in Norwood stage with MBTS. The Qp/Qs between 1.5 and 2.2 with a median of 1.75 seems to be optimal in the patients in PS2. Qp/Qs of <1.5 is associated with pulmonary stenosis, shunt stenosis, and pulmonary hypertension.